Iplementasi Strategi Mimicrymemorization pada Pembelajaran Mufradat Bahasa Arab bagi Siswa Madrasah Ibtidaiyahmin 7 Bandar Lampung - Koderi Koderi; Erni Zuliana; Arif Budiman (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2021)
Abstract This research was motivated by the difficulty and weakness of the Ibtidaiyah students' mastery of mufradat in learning Arabic. The formulation of the application "How to apply the mimicry memorization strategies to improve the mastery of Arabic mufradat for third grade students of Islamic Senior High School? The research objective was to see whether the Memorization Mimicry strategy was able to improve the students' mastery of Arabic mufradat in Madrasah Ibtidaiyah. This research uses Classroom Action Research, two cycles, each cycle of two meetings, with stages of planning, implementation, observation and reflection. The research subjects of class III MIN 7 Bandar Lampung, according to the understanding of 24 people. Observation data techniques, documentation and tests. The data analysis used was descriptive, namely data reduction, data presentation and conclusions. The results showed an increase in students' mastery of mufradat, namely that in the first cycle the average score of the students was 50% and the second cycle increased to 71%. The application that the application of the mimicry memorization strategy can improve the mastery of Arabic mufradat in Madrasah Ibtidaiyah students.